PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PEDAGANG BAKULAN DI PASAR SEKETENG SUMBAWA BESAR - Hermansyah, H; Syafruddin, S (Pusat Riset dan Publikasi, 2024)
This study aims to determine the effect of working capital on the profitability of bakulan trader at Seketeng Market, Sumbawa Besar. This study used an associative method with a quantitative approach. The type of data used was quantitative data obtained directly from primary sources using structured interview techniques. The respondents who were the sources in this study were bakulan trader at Seketeng Market, Sumbawa Besar, totaling 26 people. Data analysis in this study was carried out using the SPSS program to be interpreted using the simple linear regression analysis method, partial hypothesis testing (t-test), and determinant coefficient testing (R2). The results of this study showed that working capital had a positive and significant effect on the profitability of bakulan trader at Seketeng Market, Sumbawa Besar. This means that the greater the working capital used to run a business, the higher the level of profit obtained by traders. Conversely, the smaller the working capital used to run a business, the lower the level of profit obtained by traders. The degree of effect of the working capital variable on the profitability of bakulan trader at Seketeng Market, Sumbawa Besar was 42.9%, while the remaining 57.1% was effected by other variables outside this study model, such as length of business, capital structure, sales growth, and company size.